Structure for Architects : A CASE STUDY IN STEEL, WOOD, AND REINFORCED CONCRETE DESIGN - Bedi, Ashwani, author; Dabby, Ramsey, author (New York, NY ; Abingdon, UK : Routledge, 2020)
Includes bibliographical references and index.